2006
DOI: 10.1152/ajpendo.00582.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear progesterone receptor A and B isoforms in mouse fallopian tube and uterus: implications for expression, regulation, and cellular function

Abstract: Progesterone and its interaction with nuclear progesterone receptors (PR) PR-A and PR-B play a critical role in the regulation of female reproductive function in all mammals. However, our knowledge of the regulation and possible cellular function of PR protein isoforms in the fallopian tube and uterus in vivo is still very limited. In the present study, we revealed that equine chorionic gonadotropin (eCG) treatment resulted in a time-dependent increase in expression of both isoforms, reaching a maximal level a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 80 publications
4
49
1
Order By: Relevance
“…To standardize the assay for measurement of ER proteins, we examined different starting protein concentrations for each sample. This study demonstrated the linearity and validity of ADU for all immunoreactive bands in Western blot analysis (55,57). All steps were carried out at room temperature unless otherwise stated.…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…To standardize the assay for measurement of ER proteins, we examined different starting protein concentrations for each sample. This study demonstrated the linearity and validity of ADU for all immunoreactive bands in Western blot analysis (55,57). All steps were carried out at room temperature unless otherwise stated.…”
Section: Methodsmentioning
confidence: 65%
“…The aim of experiment 2 was to examine whether exogenous estrogens regulated ER␣ isoform expression in mouse fallopian tubes; 26-day-old female mice, in which endogenous concentrations of E 2 were expected to be minimal (55,57), were given a single subcutaneous (sc) injection of 0. The aim of experiment 3 was to determine the effect of the steroidal ER antagonist ICI 182,780 (Faslodex; fulvestrant) (21) and progesterone (P 4) on the regulation of ER␣ isoform expression in the fallopian tube; 26-day-old female mice received either E 2 (0.5 g/g BW sc) or PPT (100 g/g BW sc) for 4 days and, in addition, an intraperitoneal injection of either 8.3 mg ICI 182,780 (Tocris Cookson)/ kg BW, 2.5 mg P 4/each animal in 100 l of sesame oil (vehicle), or vehicle alone for 1-2 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To standardize the assay for the measurement of AR proteins, we examined different starting protein concentrations for individual sample. This study demonstrated the linearity and validity of ADU for all immunoreactive bands in western blot analysis (Shao et al 2006). All steps were carried out at room temperature, unless otherwise stated.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 60%
“…The protein preparation of the selected VP lobes was essentially performed as described previously (Shao et al 2006(Shao et al , 2007. The protein content was determined using the BCA protein assay (Pierce, Rockford, IL, USA).…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%